THE TRANSLATION PROCEDURE IN CHILDREN NOVEL – SPIDERWICK CHRONICLE - Larasaty, Gina (Wiralodra English Journal, 2019)
This research aims to find translation procedures from English to Indonesian which are used in translating Spiderwick Chronicles novel. The translator translates from source language (English) to target language (Indonesia). The researcher used the descriptive qualitative method to analyze the data, relates to the aim of this research is to find out the categories of translation procedure in Spiderwick Chronicle Novel. The researcher used the translation procedure (Newmark, 1988:82-91) framework by Peter Newmark for examining the data. Based on the result from the analysis showed that the total number Newmark?s translation procedure applied in Spiderwick Novel is 59 .  The most translation procedure applied is shift or transposition  with 20  (33,9%),  and the least of translation procedure applied  are Cultural equivalent , synonymy and functional  equivalent with the total frequency  1 (1,7%).  The translator used modulations as the second most translation procedure applied in the Spiderwick novel with 14 (23,7%). .